METAPHYSICAL UNDERPINNINGS AND NORMATIVE FRAMEWORKS: A THOROUGH COMPARATIVE EXAMINATION OF ISLAMIC AND WESTERN PHILOSOPHICALPARADIGMS ON THE FOUNDATIONS AND APPLICATION OF HUMAN RIGHTS - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This comprehensive study delves into a meticulous comparative analysis, examining the metaphysical underpinnings and normative frameworks inherent in Islamic and Western philosophical paradigms. The primary focus is on their profound implications for the foundations and practical application of human rights. Through an in-depth exploration of key philosophical texts, historical contexts, and real-world applications, this research sheds light on the complex tapestry that shapes understanding human rights in these distinct traditions. The Islamic viewpoint, deeply rooted in the sacred Qur'an and Sunnah, emphasizes concepts like fitrah (innate predisposition) and stewardship. At the same time, Western traditions, evolving across classical to Enlightenment eras, prioritize individual liberties within a secular framework. By navigating these intellectual landscapes, this study contributes significantly to a nuanced and culturally sensitive discourse on human rights, surpassing simplistic dichotomies and fostering a global understanding.